Spatial Navigation Impairment Is Associated with Alterations in Subcortical Intrinsic Activity in Mild Cognitive Impairment: A Resting-State fMRI Study - Zhao Qing; Weiping Li; Zuzana Nedelska; Wenbo Wu; Fangfang Wang; Renyuan Liu; Hui Zhao; Weibo Chen; Queenie Chan; Bin Zhu; Yun Xu; Jakub Hort; et al. (Behavioural Neurology)
Impairment of spatial navigation (SN) skills is one of the features of the Alzheimer’s disease (AD) already at the stage of mild cognitive impairment (MCI). We used a computer-based battery of spatial navigation tests to measure the SN performance in 22 MCI patients as well as 21 normal controls (NC). In order to evaluate intrinsic activity in the subcortical regions that may play a role in SN, we measured ALFF, fALFF, and ReHo derived within 14 subcortical regions. We observed reductions of intrinsic activity in MCI patients. We also demonstrated that the MCI versus NC group difference can modulate activity-behavior relationship, that is, the correlation slopes between ReHo and allocentric SN task total errors were significantly different between NC and MCI groups in the right hippocampus (interaction F=4.44, p=0.05), pallidum (F=8.97, p=0.005), and thalamus (F=5.95, p=0.02), which were negative in NC (right hippocampus, r=−0.49; right pallidum, r=−0.50; right thalamus, r=−0.45; all p<0.05) but absent in MCI (right hippocampus, r=0.21; right pallidum, r=0.32; right thalamus r=0.28; all p>0.2). These findings may provide a novel insight of the brain mechanism associated with SN impairment in MCI and indicated a stage specificity of brain-behavior correlation in dementia. This trial is registered with ChiCTR-BRC-17011316.